2019
DOI: 10.1128/jb.00286-19
|View full text |Cite
|
Sign up to set email alerts
|

The BvgS PAS Domain, an Independent Sensory Perception Module in the Bordetella bronchiseptica BvgAS Phosphorelay

Abstract: To detect and respond to the diverse environments they encounter, bacteria often use two-component regulatory systems (TCS) to coordinate essential cellular processes required for survival. In pathogenic Bordetella species, the BvgAS TCS regulates expression of hundreds of genes, including those encoding all known protein virulence factors, and its kinase activity is essential for respiratory infection. Maintenance of BvgS kinase activity in the lower respiratory tract (LRT) depends on the function of another … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…ChiS has a C-terminal PAS domain (SI Appendix, Fig. S10A), which may modulate ChiS enzymatic activities through small ligand binding or mediating protein-protein interactions as described for other HKs (29,30). The complex regulation of ChiS activity may serve to integrate additional cues that ultimately control expression of the chitin utilization program.…”
Section: Discussionmentioning
confidence: 99%
“…ChiS has a C-terminal PAS domain (SI Appendix, Fig. S10A), which may modulate ChiS enzymatic activities through small ligand binding or mediating protein-protein interactions as described for other HKs (29,30). The complex regulation of ChiS activity may serve to integrate additional cues that ultimately control expression of the chitin utilization program.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the reason for the presence of a PAS domain in BvgS might go beyond facilitating the shift between states of activity. Signal perception and mechanical transmission are not mutually exclusive, and several cytoplasmic PAS domains are involved in sensing, particularly energy pathways (42,43). We screened a library of small molecules using a thermal shift assay but could not identify bona fide ligands of the BvgS PAS domain (E. Lesne, personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…Dupré et al concluded that the major function of the PAS domain is to maintain the conformational tension imposed by the periplasmic moiety of BvgS [157]. A recent study suggested that the BvgS PAS domain may function as an independent signal perception domain, as shown by in vivo animal experiments using B. bronchiseptica strains with mutations in the PAS domain [158].…”
Section: Othersmentioning
confidence: 99%